Hidden crisis in higher education - Hussain Ismail, A.G. (2011)
Universities ceremonially celebrate the success and pay less attention to dropouts and non completers. It is a general scenario that, universities in the world experience a high rate of non completion among the Doctoral research students, which will have a high impact on the university and the individual students. A major study is being carried out by the author of this paper on 'International students studying at universities In Malaysia are at risk', with a sample of 300 PhD students selected from two state universities and two private universities in Malaysia, which included completers and non completers who to registered for Doctoral Research Program. This paper attempts to analyse some of the findings of a pilot study conducted as a part a non major study with 30 PhD students and debates whether the non completion is an individual problem or the Institution also have a role to play in their success. Further, the paper intends to suggest some strategies to mitigate the risk.